If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -7) + 5 = 5 + -1(3 + -2x) Reorder the terms: 2(-7 + x) + 5 = 5 + -1(3 + -2x) (-7 * 2 + x * 2) + 5 = 5 + -1(3 + -2x) (-14 + 2x) + 5 = 5 + -1(3 + -2x) Reorder the terms: -14 + 5 + 2x = 5 + -1(3 + -2x) Combine like terms: -14 + 5 = -9 -9 + 2x = 5 + -1(3 + -2x) -9 + 2x = 5 + (3 * -1 + -2x * -1) -9 + 2x = 5 + (-3 + 2x) Combine like terms: 5 + -3 = 2 -9 + 2x = 2 + 2x Add '-2x' to each side of the equation. -9 + 2x + -2x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 + 0 = 2 + 2x + -2x -9 = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -9 = 2 + 0 -9 = 2 Solving -9 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| V+5=23 | | 4x+13=7x-8 | | (Y-9)-(y+3)=4y | | -3(2q+2)= | | (x+2)+(9x-52)=180 | | 25000+3000n=36000+2000n | | 11+4x=2(11+4x) | | 0.3-2=7 | | 3x+2(x-1)=2 | | 4x+12-3x=19 | | 4x^4-4x^3-25x^2+x+6=0 | | 5/9x-1/3=1/5 | | 18+2=44 | | 3x-3+9=5x-7-3x | | 9x+3=7x+8 | | 6p+7q=39 | | (2x+66)=(8x+6) | | 7v+10=8v+v | | m^2=-3m+18 | | -21=0.5c-11 | | 17+w=94 | | p+.3p=.6 | | x^4-2x^3+x^2-4=0 | | 2x^2+9x=6x+20 | | 0.08(3v-4)=0.4(v-4) | | 3(v+8)-10v=-7v-42 | | 4+0.6x=16 | | 20x-6=40x+6 | | -78+n=-133 | | 2x+42+1+3x-31=180 | | -6(-6+5x)-6(x-7)=x+3+7-3x | | x^3-4x^3+3x=0 |